C-Arm CT Measurement of Cerebral Blood Volume Using Intra-Arterial Injection of Contrast Medium: An Experimental Study in Canines - Yasuda, R. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Measurement of perfusion parameters is typically done using an intravenous injection of contrast medium. This purpose of this study was to evaluate the feasibility of measuring regional and global CBV using C-arm CT with IA injections of contrast medium. MATERIALS AND METHODS: Twelve canines were studied. CBV measurement was performed using standard PCT, and then using C-arm CT with IV and IA contrast. Values obtained using C-arm CT were compared with those using PCT. RESULTS: C-arm CT CBV maps using IA injections required less contrast than ones with IV injections. PCT and C-arm CT using IV and AA injections provided comparable maps. In controls, C-arm CT with a CCA or VA injection provided comparable maps to PCT. In animals with a stroke, a CCA or VA injection did not provide maps comparable to ones made with PCT. IV and AA C-arm CT showed excellent quantitative agreement with PCT, while CCA and VA C-arm CT studies did not. CONCLUSIONS: Measurement of global CBV using C-arm CT in conjunction with either an IV or an AA injection was feasible in controls and dogs with a stroke. Measurement of regional CBV with C-arm CT using either CCA or VA injection, in normal canines, provided CBV maps qualitatively comparable with those obtained with PCT; the absolute CBV values from these maps were in poor agreement with PCT measurements. Valid measurement of CBV using C-arm CT requires all tissue in a target region to be fully and equally opacified during any acquisition. Using CCA or VA injections, it was impossible to document if and when this had been achieved. CBV measurements using these routes of injection were therefore not reliable.